2008
DOI: 10.1002/hyp.6929
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry of the Narmada and Tapti Rivers, India

Abstract: The chemistry of major ions and elements in Narmada and Tapti river water was studied based on the monitoring of the drainage basins for monsoon and post-monsoon seasons in 2004. The results show the influence of rock weathering on the concentration of major ions in the surface water. There is a significant contribution from the catchment geologies in the major constituents of water. The total dissolved solids (TDS) concentrations are reflecting the signature of weathering of rocks in the catchment areas. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The increase in HCO − 3 concentration can be attributed to seasonal variability in chemical weathering of carbonate and silicate minerals (Tipper et al 2006) or redissolution of precipitated salt in the post-monsoon season induced by rain water and water level rise (Rengarajan et al 2009). However, increase in NO − 3 concentration may be attributed to degradation of organic matter and/or anthropogenic sources including runoff from surrounding agricultural fields and untreated sewage (Sharma and Subramanian 2008). There is no significant variation in the concentration of Mg 2+ , K + and SO 2− 4 , reflecting their conservative behaviour in the basin.…”
Section: Seasonal and Spatial Variations In Major Ionsmentioning
confidence: 84%
See 1 more Smart Citation
“…The increase in HCO − 3 concentration can be attributed to seasonal variability in chemical weathering of carbonate and silicate minerals (Tipper et al 2006) or redissolution of precipitated salt in the post-monsoon season induced by rain water and water level rise (Rengarajan et al 2009). However, increase in NO − 3 concentration may be attributed to degradation of organic matter and/or anthropogenic sources including runoff from surrounding agricultural fields and untreated sewage (Sharma and Subramanian 2008). There is no significant variation in the concentration of Mg 2+ , K + and SO 2− 4 , reflecting their conservative behaviour in the basin.…”
Section: Seasonal and Spatial Variations In Major Ionsmentioning
confidence: 84%
“…These studies also explain the exogenic cycling of elements in the continent-river-ocean Kump 1994;Zhang et al 1995;Galy and FranceLanord 1999;Hren et al 2007;Li et al 2009). Indian rivers have also been studied to understand (i) hydrological and environmental characteristics of river basins, (ii) influence of basin geology, tectonics, climate and anthropogenic activities on riverine chemistry and (iii) elemental fluxes from rivers to oceans (Subramanian 1979(Subramanian , 1983Biksham and Subramanian 1988;Sarin et al 1989;Chakrapani and Subramanian 1990;Ramanathan et al 1994;Krishnaswami and Singh 1998;Ahmad et al 1998;Singh and Hasnain 1999;Dalai et al 2002;Singh et al 2005;Sharma and Subramanian 2008;Jha et al 2009;Rengarajan et al 2009;Gupta et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…This is due to the fact that the rate of carbonate weathering dominates that of silicate weathering in a river basin (Gaillardet et al 1999). This has been reported by Sharma and Subramanian (2008) which conclude that the chemical composition of Narmada river is more controlled by the carbonate lithology of the basin, which is present as intrusive complexes and dykes, along the minor rift zones in the Deccan Volcanic Province with neighbouring carbonate-alkaline complexes.…”
Section: Dissolved Trace Metals and Nutrients In Watermentioning
confidence: 64%
“…The nature and flux of organic C and P in Indian rivers has been studied by few authors (Gupta et al 1997;Ramesh et al 1995). Study of major ions in the waters of Narmada and Tapti rivers has already been reported (Sharma and Subramanian 2008), and limited data exist on trace metal pollution in sediments of the Narmada river basin (Jain et al 2008). The objective of this study, therefore, was to establish the nature of distribution of dissolved trace metals (Cd, Cu, Pb, Zn, Fe, Ni, Cr, Mn, and As) and nutrients such as dissolved organic carbon (DOC), dissolved inorganic nitrogen (NO 3 -), dissolved inorganic phosphorus (PO 4 3-), and dissolved silica (H 4 SiO 4 ) highlighting the potential risk of their elevated concentrations on the aquatic organism and human beings.…”
Section: Introductionmentioning
confidence: 97%
“…The trend indicates that groundwater is in disequilibrium with the atmosphere. The groundwater pCO 2 in the study area are higher than those reported in case of surface waters (Sharma and Subramanian 2008 ). This increase in pCO 2 would typically be counterbalanced by mineral weathering reactions in the aquifer.…”
Section: Weathering Processes and Evolution Of Groundwater Chemistrymentioning
confidence: 85%